Global norms on the elimination of violence against women - Lars Engberg-Pedersen (Danish Institute for International Studies (DIIS), 2021)
Do global norms change? This paper argues that the global norms on the elimination of violence against women first agreed upon in connection with the adoption of the Declaration on the Elimination of Violence against Women in 1993 have changed in subsequent agreements at the UN. These agreements include the Beijing Declaration and Platform for Action of the Fourth World Conference on Women, 1995; the agreed conclusions of the 42nd session of the Commission on the Status of Women (CSW42), 1998; the agreed conclusions of the 57th session of the Commission on the Status of Women (CSW57), 2013; and the agreed conclusions of the 65th session of the Commission on the Status of Women (CSW65), 2021. The agreements are analysed in detail using a methodology based on interpretative content analysis. Five different elements of the normative regime associated with the issue are identified. They have to do with framework, responsible actors, approach, sites, and definition of violence against women. In relation to three of these normative elements, significant change has taken place since 1993. This paper does not put the findings into theoretical context or analyse the causes of normative change.
Keywords: 330; Development policy